A STUDY ON ECONOMIC IMPACT OF V.O. CHIDAMBARANAR PORT ON THE DEVELOPMENT OF THOOTHUKUDI DISTRICT - Dr. M. THIRUMATHI ,Dr. N. KRISHNAN (Journal of Computational Analysis and Applications (JoCAAA), 2024)
This study examines the economic impact of V.O. Chidambaranar Port on the development ofThoothukudi District. The port plays an important role in promoting trade, industrial growth,employment generation and regional economic development. It facilitates the movement of various commodities, supports import and export activities